2017
DOI: 10.1186/s12978-017-0303-8
|View full text |Cite
|
Sign up to set email alerts
|

Medical termination of pregnancy in general practice in Australia: a descriptive-interpretive qualitative study

Abstract: BackgroundAustralian Government approval in 2012 for the use of mifepristone and misoprostol for medical termination of pregnancy (MTOP) allows general practitioners (GPs) to provide early gestation abortion in primary care settings. However, uptake of the MTOP provision by GPs appears to be low and the reasons for this have been unclear. This study investigated the provision of and referral for MTOP by GPs.MethodsWe undertook descriptive-interpretive qualitative research and selected participants for diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 20 publications
4
52
0
Order By: Relevance
“…The presence of local allied health professionals and diagnostic facilities, required for the assessment of MA eligibility and the management of non‐life‐threatening complications, is essential for the improvement of abortion access in regional and rural areas. Consistent with previous research, this study indicates a lack of these support systems in regional and rural areas of Victoria, which can contribute to lower health outcomes for Australian residents in rural and regional communities compared with people living in metropolitan areas . The study participants specifically expressed their concern about the lack of a 24‐hour contact advice service, insufficient access to after‐hour care and surgical back‐up in case of complications, and the lack of local ultrasound availability, required for pregnancy dating and the exclusion of ectopic pregnancies .…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The presence of local allied health professionals and diagnostic facilities, required for the assessment of MA eligibility and the management of non‐life‐threatening complications, is essential for the improvement of abortion access in regional and rural areas. Consistent with previous research, this study indicates a lack of these support systems in regional and rural areas of Victoria, which can contribute to lower health outcomes for Australian residents in rural and regional communities compared with people living in metropolitan areas . The study participants specifically expressed their concern about the lack of a 24‐hour contact advice service, insufficient access to after‐hour care and surgical back‐up in case of complications, and the lack of local ultrasound availability, required for pregnancy dating and the exclusion of ectopic pregnancies .…”
Section: Discussionsupporting
confidence: 74%
“…Previous research suggests that Australian GPs anticipate negative publicity and reactions from conservative members of the community as well as from other health professionals, if they were to provide abortion services. Community‐level abortion stigma as well as practice restrictions, imposed by ideologically opposed colleagues, thus might influence health workers in their decision to provide abortion care, especially in rural and regional communities where sexual and reproductive health, including abortion, is still a highly contentious topic .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Australia also continues to experience a variety of regulatory barriers depending on geographic location and research has indicated that these regulations limit provision of medical abortion by primary care professionals. [11] When the Canadian restrictions were announced, advocates for abortion access raised concerns that they would limit particularly the potential for primary care provision and thus access to abortion. Further, there was no evidence that the restrictions would improve patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…It was hoped that with subsidy of mifepristone and misoprostol through the Pharmaceutical Benefits Scheme in 2013, coupled with the provision of accredited online training for GPs in the delivery of medical abortion, that improvements in access, especially for women in rural areas, would occur through GP provision. However, uptake in general practice appears to be low with a recent NSW‐based qualitative study suggesting reasons for this ranging from from the belief that medical abortion is beyond the scope of general practice, to fears of community stigma and the perception that provision is complicated . While medical abortion will not be within the scope of all GP practices, support by local gynaecologists and hospital services for those who do want to provide this service is imperative in the event that specialist back‐up is required.…”
mentioning
confidence: 99%